13(18)‐Ene ursan glycosides from Allium ascalonicum. Issue 1 (26th February 2020) - Mai, Nguyen Thi; Lan, Hoang Thi Tuyet; Trang, Do Thi; Dung, Duong Thi; Tai, Bui Huu; Nhiem, Nguyen Xuan; Van Kiem, Phan
Abstract: Allium ascalonicum L. is belong to Alliaceae family, which is common vegetables and used to treat typhoid, colds, headaches, bloating and poisoning, eyes blurred deaf ears, burnt blood, pregnant women, breast swelling, children wicked and swollen in folk medicine. Using combined chromatographic methods, four 13, 18‐en ursan compounds were isolated from methanol extract of the roots of Allium ascalonicum . Their chemical structures were elucidate as 3 β, 12 α, 19 α ‐trihydroxyurs‐13(18)‐en‐28, 20β‐lactone (1 ), 3 β, 12 α, 19 α ‐trihydroxyurs‐13(18)‐ene‐28, 20 β ‐lactone‐3‐ O ‐(3‐ O ‐ β ‐D‐glucopyranosyl‐2‐ O ‐ α ‐L‐rhamnopyranosyl)‐ α ‐L‐arabinopyranoside (2 ), 3 β, 12 α, 19 α ‐trihydroxyurs‐13(18)‐ene‐28, 20 β ‐lactone‐3‐ O ‐[3‐ O ‐( β ‐D‐glucopyranosyl‐2‐ O ‐ β ‐D‐glucopyranosyl)‐2‐ O ‐ α ‐L‐rhamnopyranosyl]‐ α ‐L‐arabinopyranoside (3 ), 3 β, 12 β, 19 α ‐trihydroxyurs‐13(18)‐ene‐28, 20 β ‐lactone‐3‐ O ‐(3‐ O ‐ β ‐D‐glucopyranosyl‐2‐ O ‐ α ‐L‐rhamnopyranosyl)‐ α ‐L‐arabinopyranoside (4 ) on the basis of spectroscopic evidences and in comparison with those reported in the literature. All these compounds were isolated from Allium genus for the first time.